PENGGUNAAN MEDIA POWER POINT DALAM PEMBELAJARAN MATEMATIKA DAN PENGARUHNYA TERHADAP PRESTASI BELAJAR SISWA - Nurhayati, Nurhayati; Arafat, Yasir; Fitriani, Yessi (Jurnal Ilmiah Bina Edukasi, 2020)
This research aims to determine the effect of using powerpoint media in mathematics learning on student achievement in Madrasah Tsanawiyah Ogan Ilir. This research uses quantitative methods with quasi experimental research types. The population of the study was 221 people, students of class VIII at MTs Negeri 2 Tanjung Raja, Ogan Ilir District. The number of research samples were 72 people. The sampling technique in this study is a nonprobability sampling technique with a type of purposive sampling technique. Data collection techniques using the test model, namely pretest and posttest in the experimental class and the control class. Data were analyzed using simple linear regression analysis analysis techniques. The results showed that there was a significant influence on the use of powerpoint learning media in mathematics learning on student achievement in MTs Negeri 2 Tanjung Raja, Ogan Ilir District.